Mali : Seventh Review Under the Extended Credit Facility and Request for a new Three-Year Arrangement Under the Extended Credit Facility: Staff Report; Joint IDA/IMF Debt Sustainability Analysis; Informational Annex; Statement by IMF Staff Representative; Statement by Alternate Executive Director for Mali; and Press Releases. (IMF Staff Country Reports; Country Report, 2012)
In 2011, the economy of Mali is expected to stay on a robust growth trajectory with low inflation. Fiscal performance has been consistent with program targets during the first half of 2011. Money supply increased more than GDP during the first nine months of 2011. The authorities intend to continue the ongoing economic and financial reforms in cooperation with the IMF. Initiation of the new Extended Credit Facility program will coincide with the launch of the third growth and poverty reduction strategy (G-PRSP III) for 2012-17.